diff --git a/.obsidian/plugins/obsidian-git/data.json b/.obsidian/plugins/obsidian-git/data.json index bef4c6e..e69de29 100644 --- a/.obsidian/plugins/obsidian-git/data.json +++ b/.obsidian/plugins/obsidian-git/data.json @@ -1,27 +0,0 @@ -{ - "commitMessage": "vault backup: {{date}}", - "autoCommitMessage": "vault backup: {{date}}", - "commitDateFormat": "YYYY-MM-DD HH:mm:ss", - "autoSaveInterval": 5, - "autoPushInterval": 0, - "autoPullInterval": 5, - "autoPullOnBoot": true, - "disablePush": false, - "pullBeforePush": true, - "disablePopups": false, - "listChangedFilesInMessageBody": false, - "showStatusBar": true, - "updateSubmodules": false, - "syncMethod": "merge", - "customMessageOnAutoBackup": false, - "autoBackupAfterFileChange": false, - "treeStructure": false, - "refreshSourceControl": true, - "basePath": "", - "differentIntervalCommitAndPush": false, - "changedFilesInStatusBar": false, - "showedMobileNotice": true, - "refreshSourceControlTimer": 7000, - "showBranchStatusBar": true, - "setLastSaveToLastCommit": false -} \ No newline at end of file diff --git a/education/math/MATH1210 (calc 1)/Derivatives.md b/education/math/MATH1210 (calc 1)/Derivatives.md index 6b1f876..6b6ed7e 100644 --- a/education/math/MATH1210 (calc 1)/Derivatives.md +++ b/education/math/MATH1210 (calc 1)/Derivatives.md @@ -139,19 +139,28 @@ This is used when you want to take the derivative of a function raised to a func 1. $\dfrac{d}{dx} x^x$ 2. $y = x^x$ -3. $\ln y = \ln x^x$ +3. Take the natural log of both sides: $\ln y = \ln x^x$ 4. $\ln(y) = x*\ln(x)$ -5. $\dfrac{d}{dx} \ln y = \dfrac{d}{dx} x \ln x$ -6. $\dfrac{1}{y} \dfrac{dy}{dx} = 1 * \ln x + x * \dfrac{1}{x}$ +5. Use implicit differentiation: $\dfrac{d}{dx} \ln y = \dfrac{d}{dx} x \ln x$ +6. Solve for $\dfrac{dy}{dx}$: $\dfrac{1}{y} \dfrac{dy}{dx} = 1 * \ln x + x * \dfrac{1}{x}$ +7. $\dfrac{dy}{dx} = (\ln x + 1) * y$ +8. Referring back to step 2, $y = x^x$, so the final form is: +9. $\dfrac{dy}{dx} = (\ln(x) + 1)x^x$ + +### Examples +> Find the derivative of the function $y = (2x \sin x)^{3x}$ + +1. $\ln y = \ln (3x \sin x)^{3x}$ +2. $\ln y = 3x * ln(2x \sin x)$* # Chain Rule $$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$ ## Examples > Given the function $(x^2+3)^4$, find the derivative. Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$. -7. First find the derivative of the outside function function ($f(x) = x^4$): +3. First find the derivative of the outside function function ($f(x) = x^4$): $$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...$$ -8. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$. +4. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$. $$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$ > Apply the chain rule to $x^4$ @@ -187,7 +196,7 @@ $$ \dfrac{d}{dx} \cot x = -\csc^2 x $$ - Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$. Given these facts: -9. Let $y$ be some function of $x$ -10. $\dfrac{d}{dx} x = 1$ -11. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\ +5. Let $y$ be some function of $x$ +6. $\dfrac{d}{dx} x = 1$ +7. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\